Analysis of the financial efficiency of companies in the industrial sector during COVID- 19: Case study in Peru - Sovero Rivera, Lucero Emperatriz (2022)
The pandemic has created an environment of considerable uncertainty, forcing companies to efficiently manage their resources to optimize their profits, prevent falling revenues, sustain the chain of payments and preserve employment. The objective of this research is to apply the Data Envelopment Analysis (DEA) method to know the financial impact of the COVID-19 crisis on Peruvian companies in the industrial sector, which are listed on the Bolsa de Valores de Lima. Multi-criteria model and correlation analysis were used for the validation of financial ratios, DEA method was used to evaluate efficiencies and Malmquist Productivity Index (MPI) to analyze changes in performance by quarter. Results indicate that 77% of companies are inefficient, equity items and administrative expenses are the most crucial for these companies to improve their performance; in addition, there is a deterioration of -31.5% in the total productivity of the sector mainly caused by the decrease in technological progress. This research offers decision-makers a tool that allows them to devise strategies to face the continuing financial crisis and promote investment in the use of technologies that may contribute to the improvement of productivity.